THE SUPERIOR SEMICIRCULAR CANAL DEHISCENCE SYNDROME: ARTIGO DE REVISÃO - Vianas Gomes, Weidmmer Rogério (2018)
The Superior semicircular canal dehiscence syndrome is a rare disease (little study in Brazil) and that in the first aspect, in 1998 by Minor et al. was described as a degradation of the bone layer responsible for coating the upper semicircular canal. It is directly correlated to vestibular symptoms and some patients may present euphonia and loss hearing. It is worth noting that the etiopatology of the disease has not yet beenpercentage of those who are symptomatic, demonstrating the peculiarity of the syndrome in question. On the other hand, there are hypotheses that believe that the error development of the bone layer that covers the semicircular canal. As a diagnosis, it is understood that the clinical examination is of paramount importance, because the stipulated examinations as gold standard are not able to expose significant changes. When a suspect individuals should be submitted to the evaluation protocol with the to be confirmed the HD (diagnostic hypothesis). Finally, it is understood that SDCSS should be included among the causes of vertigo such as transmission hypoacusis and although it is an unusual alteration, there are several physiopathological aspects not yet written. It has the advantage of avoiding inappropriate therapeutic approaches. (Minor et al, 2001)